The Impact of Female Directors on the Relationship Between Corporate Social Responsibility and Capital Structure: Evidence From Egypt - Khalil, Manal; Rashed, Ahmed (Journal of Applied Business and Economics, 2023)
This paper examines how corporate social responsibility affects capital structure. The sample consists of 58 non-financial companies listed on the Egyptian Stock Exchange, with 464 firm-year observations made between 2014 -2021 using the generalized method of moments and ordinary least squares. Data was gathered from reports and financial statements from an Egyptian information dissemination firm. This paper demonstrates that firms with female directors explain the negative impact of the association between corporate social responsibility and capital structure. Female directors and CSR disclosure improve manager oversight and reduce information asymmetry and agency conflicts. Results support agency and gender theories that expect different behavior from women in leadership posts.